Characterization and identification of metabolites in three types of Malaysian stingless bee honeys and their roles in reducing heterocyclic amines in grilled beef - Shamsudin, Sharina (2019)
Honey is known as a potential source of natural antioxidants, especially stingless bee honey. However, antioxidant content, as well as its physicochemical properties, are greatly influenced by botanical origin. Furthermore, honey has been used in meats to reduce the formation of heterocyclic amines (HCAs) during cooking. The first objective of this study was to compare the physicochemical and antioxidant properties of stingless bee honey from different botanical origins and authenticate their origins. The physicochemical characteristics (moisture content, pH, free acidity, total soluble solids, colour, 5-hydroxymethylfurfural, amino acid content and sugar content) and antioxidant properties (total phenolic content, total flavonoids content, free radical scavenging activity (DPPH assay), and ferric reducing antioxidant power (FRAP assay)) of stingless bee honey produced by Heterotrigona itama from different botanical origins (acacia, starfruit and gelam) and Apis mellifera honey (control) were investigated. Stingless bee honey had significantly higher moisture content and free acidity, as well as antioxidant capacity and activity compared to A. mellifera honey. Gelam honey had the highest antioxidant activity and significantly different to other honey samples studied. Moreover, partial least squares-discriminant analysis (PLS- DA) model had successfully discriminated among stingless bee honey and showed that stingless bee honey was distinguishable from A. mellifera honey based on amino acid content. The second objective was to determine the inhibitory effect of stingless bee honey containing marinade on HCAs formation. Tenderloin beef meat was separately marinated with acacia, starfruit, gelam and A. mellifera honey-containing marinades at 4 °C for 24 h prior to gas grilled at 265±5 °C for 3.5 min per side. The concentrations of amino acids, sugars and creatinine in marinated beef samples were measured. The HCAs concentration in grilled beef was determined by using high-performance liquid chromatography (HPLC). The beef samples marinated with table sugar-containing marinade were used as a reference sample. The results showed that both total HCAs and individual HCAs were alleviated in grilled beef samples marinated with honey as compared to grilled beef samples marinated with table sugar. Gelam honey showed the highest inhibition and was significantly different to other samples. The inhibition rates of total HCAs were 95.14%, 88.45%, 85.65% and 57.22% for grilled beef samples marinated with gelam, starfruit, acacia and A. mellifera honey, respectively. The complete inhibitory effect was observed for MeIQx (100%) in gelam and starfruit honey. Meanwhile, for 4,8-DiMeIQx, PhIP, norharman, harman and AαC, the inhibition achieved up to 79.59%, 94.44%, 96.20%, 83.79% and 95.94%, respectively, regardless of the botanical origins of the honey. Antioxidant activity was found as the main factor that affected HCAs formation as it had strong (r = 0.964) and significant (p < 0.05) correlation with HCAs concentration. This indicated that stingless bee honey is effective to reduce toxic and harmful HCAs formed in grilled beef. The last objective was to identify the potential metabolites in stingless bee honey related to HCAs suppression using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS)-based metabolomics approaches. All honey samples were subjected to gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-quadrupole-time-of-flight-mass spectrometry (LC- QTOF-MS) analyses to obtain the metabolite profiles of all honey samples. Chemometrics analysis was performed by correlating the metabolites detected with the bioactivity of honey samples using orthogonal partial least squares (OPLS) model. Seven bioactive compounds were identified from GC-MS data, namely pinitol, mannitol, myo-inositol, gluconic acid, glucose, fructose and maltose. Meanwhile, LCMS identified five compounds: 3-hydroxy-4,4-dimethyloxolan-2-one; 2- (hydroxymethyl)-1-methylpiperidine-3,4,5-triol; 3-carboxy-2,3-dideoxy-pentaric acid; 3-phenyl-2-propenoic acid phenylmethyl ester and 1,3-bis(4-methoxyphenyl)-2- propen-1-one. All compounds identified had a positive correlation with antioxidant activity and HCAs formation. These compounds are suggested to be accountable for HCAs inhibition in grilled beef. In conclusion, honey composition is greatly influenced by its botanical origin and bee species. Stingless bee honey is totally different from A. mellifera honey in terms of physicochemical characteristics and antioxidant properties. In addition, stingless bee honey has been proven in this study to inhibit HCAs formation in grilled beef. The ability of stingless bee honey to inhibit HCAs has a strong association with its antioxidant activity, which indicates stingless bee honey as a potential source of antioxidants and HCAs inhibitor. This finding may be useful to the food processing industry and households as a simple and practical method of achieving significant inhibition of toxigenic compounds in grilled meat.